2021
DOI: 10.18174/538961
|View full text |Cite
|
Sign up to set email alerts
|

Tools for transitions : An inventory of approaches, methods and tools for stakeholder engagement in developing transition pathways to sustainable food systems

Abstract: An inventory of approaches, methods and tools for stakeholder engagement in developing transition pathways to sustainable food systems. Wageningen, Wageningen Marine Research, Wageningen Marine Research report C001/21. This study was carried out by Wageningen University & Research and was commissioned and financed by the Dutch Ministry of Agriculture, Nature and Food Quality within the context of the Knowledge Base programme 'Food Security and Valuing Water' (Transition pathways: project number KB-35-006-001).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…Starting with an extensive list of documented mechanisms that have been used to support innovation in the broad field of agriculture, we eliminated those we perceived to be tools or approaches-tools being means to fulfill a task, and approaches being paradigms that inform the way that development or research is done (de Koning et al, 2021)-leaving a list of 12 instruments. We developed a data collection framework prior to reviewing literature and gathering information.…”
Section: Methodsmentioning
confidence: 99%
“…Starting with an extensive list of documented mechanisms that have been used to support innovation in the broad field of agriculture, we eliminated those we perceived to be tools or approaches-tools being means to fulfill a task, and approaches being paradigms that inform the way that development or research is done (de Koning et al, 2021)-leaving a list of 12 instruments. We developed a data collection framework prior to reviewing literature and gathering information.…”
Section: Methodsmentioning
confidence: 99%
“…As a result, challenges with stakeholder engagement faced by health research priority setting exercises (McGregor et al, 2014;Hauck et al, 2015) will be even more prominent in food system research priority setting. de Koning et al (2021) suggested different approaches at different level to support stakeholder engagement: an approach that recognizes the value of different types of knowledge and paradigms from different disciplines, a method that is open, inclusive, and reflexive with different steps, and tools that support exploration, positioning and identifying pathways and actions from the perspective of stakeholders.…”
Section: Challenges Of Setting Priority For Food System Researchmentioning
confidence: 99%
“…Therefore, understanding this power relation and fostering fundamental change to this power relation are key to making sure transitions become profoundly more just(Newell et al, 2021). This depth of change is what the operational framework should enable De Koning, et al (2021). andNewell et al (2021) indicated that a specific type of knowledge is needed to encourage this fundamental change in power relation: knowledge about the pluralistic norms and values in society that affects world views, knowledge about how systems are perceived and knowledge about all types of options for change.…”
mentioning
confidence: 99%